The Relationship Between Body Image in Postpartum Mothers and Practice of Breastfeeding - Laili, Uliyatul; Amalia, Rizki (Journal of Global Research in Public Health, 2020)
A negative body image can be formed because of a person’s dissatisfaction with his body shape and daily appearance. Postpartum mothers with a negative body image tend to stop breastfeeding before 6 months, because they are worried that breastfeeding will have a negative impact on their body shape. Based on this background, the researcher wants to examine the relationship between body image in postpartum mothers and the practice of breastfeeding.The research design was cross sectional analytic. The research sample was 67 postpartum mothers who were in the Sidoarjo. The results of this data collection will then be processed using a computer program. Then to determine whether there is a correlation between body image perception and the practice of breastfeeding, data analysis was carried out using the chi square test. The variables in this study include the independent variable, which is the scale of body image perception, while the dependent variable is the practice of breastfeeding.Based on the results of data analysis, it shows that the majority of respondents with a negative body image practice breastfeeding as many as 14 respondents. Based on data analysis using the chi square test, it shows that p <α, which is 0.005 <0.05, so it can be concluded that there is a relationship between body image perception and breastfeeding practice.